Corporate Social Responsibility, Environmental Social Governance, And Implementation Of Green Accounting On Firm Value - Anita Anita; Ni Nyoman Alit Triani; Dewi Prastiwi (Yayasan Riset dan Pengembangan Intelektual, 2024)
This research aims to test and analyze the influence of Corporate Social Responsibility, Environmental Social Governance, and the implementation of Green Accounting on firm value as proxied by Tobin's Q. The subjects of this research are manufacturing sector companies that are actively listed on the Indonesia Stock Exchange in the 2020-2022 period that selected through purposive sampling technique. This research uses quantitative research methods. This research has results showing that Corporate Social Responsibility has a positive effect on firm value, Environmental Social Governance has a negative effect on firm value, and Implementation of Green Accounting has no effect on firm value.